The Bahamas : Request for Purchase under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for The Bahamas. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2020)
This paper highlights The Bahamas' Request for Purchase Under the Rapid Financing Instrument (RFI). The coronavirus disease 2019 (COVID-19) pandemic comes on the heels of the widespread destruction caused by Hurricane Dorian in September 2019. Coupled with domestic containment measures, the collapse in tourism will cause a deep recession. The Bahamian authorities have taken timely and targeted measures to boost health spending and mitigate the socioeconomic impact of the pandemic, supporting jobs and vulnerable segments of the population. The disbursement under the RFI will help boost resources for essential COVID-19-related outlays, strengthen reserves, and catalyze additional support from other international financial institutions, development partners, and the private sector. In order to address the urgent fiscal needs, the central bank will on-lend the disbursement to the Ministry of Finance. The IMF staff is confident that the authorities will pursue appropriate policies for alleviating the impact of the pandemic, based on the country's strong track record. The Bahamas is assessed to have sustainable debt and adequate capacity to repay the IMF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet